Proprioception Is Necessary for Body Schema Plasticity: Evidence from a Deafferented Patient - Cardinali, Lucilla; Brozzoli, Claudio; Luauté, Jacques; Roy, Alice C.; Farnè, Alessandro (Frontiers in Human Neuroscience, 2016)
The ability of using a large variety of tools is important in our daily life. Behind human tool-use abilities lays the brain capacity to incorporate tools into the body representation for action (Body Schema, BS), thought to rely mainly on proprioceptive information. Here we tested whether tool incorporation is possible in absence of proprioception by studying a patient with right upper-limb deafferentation. We adopted a paradigm sensitive to changes of the Body Schema and analysed the kinematics of free-hand movements before and after tool-use, in three sessions over a period of two years. In the first session, before tool-use, the kinematics of the deafferented hand was disrupted. Similarly, the first movements with the tool (a mechanical grabber elongating the arm by ∼40cm) showed an abnormal profile that tended to normalize at the end of the session. Subsequent free-hand movements were also normalised. At session 2, 6 months later, the patient exhibited normal free-hand kinematic profiles, additionally showing changes in grasping kinematics after tool-use, but no sign of tool incorporation. A follow-up two years later, further confirmed the normalized kinematic profile but the absence of tool incorporation. This first description of tool-use in absence of proprioception shows the fundamental role of proprioception in the update of the Body Schema. These results provide an important further step in understanding human motor control and have implications for future development of rehabilitation programs for patients with sensory deficits